Taxonomic status of Saccostomus campestris (Rodentia: Cricetomyinae) from southern Africa : a multidisciplinary approach - Ferguson, J. Willem H. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.